2016
DOI: 10.1007/s10562-016-1697-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphology of Cerium Oxide Catalysts for Reverse Water Gas Shift Reaction

Abstract: Reverse water gas shift reaction (RWGS) was investigated over cerium oxide catalysts of distinct morphologies: cubes, rods and particles. Catalysts were characterized by X-ray diffraction, Raman spectroscopy and temperature programmed reduction (TPR) in hydrogen. Nanoshapes with high concentration of oxygen vacancies contain less surface oxygen removable in TPR. Cerium oxide cubes exhibited two times higher activity per surface area as compared to rods and particles. Catalytic activity of these nanoshapes in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 69 publications
3
47
0
2
Order By: Relevance
“…CO 2 can dissociate on the oxygen vacancies of ceria [22]. Thus, ceria can be used for RWGS alone [23], albeit at higher temperatures. The same can occur with TiO 2 , which is also a reducible support.…”
Section: Activity Measurementsmentioning
confidence: 99%
“…CO 2 can dissociate on the oxygen vacancies of ceria [22]. Thus, ceria can be used for RWGS alone [23], albeit at higher temperatures. The same can occur with TiO 2 , which is also a reducible support.…”
Section: Activity Measurementsmentioning
confidence: 99%
“…21,22 In addition, the variation of several parameters during the synthesis procedure (i.e., temperature and base concentration) can lead not only to different ceria morphologies with high shape purity, but also to structures with tunable surface areas and defect concentrations. 23 For instance, Liu et al 27 synthesized CeO 2 samples by precipitation, hydrothermal and citrate sol-gel methods. CeO 2 prepared with hydrothermal method showed larger surface area, average pore diameter and pore volume.Makinose et al 28 fabricated ceria nanoparticles (NPs) with controlled crystal orientations via an oleate-modied hydtrothermal method; by altering the molar ratio of oleate to cerium ions in the reaction solution different ceria facetes were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…These trends are further revealed by the broadening of the F 2g mode around the 460 cm À1 band. 52 A higher abundance of oxygen vacancies in the rod when compared with that of the particles indicates a more reducible surface oxygen species, which is the main factor for the photocatalytic behavior or chemical sensing. 52 are assigned to the Ce 3+ ion.…”
Section: Growth Process and Properties Of Synthetic Cerium Oxide Nanomentioning
confidence: 99%
“…52 A higher abundance of oxygen vacancies in the rod when compared with that of the particles indicates a more reducible surface oxygen species, which is the main factor for the photocatalytic behavior or chemical sensing. 52 are assigned to the Ce 3+ ion. Further, it can be observed that the mixed valence state of Ce 4+ and Ce 3+ ions were present as satellites, and the ratio of Ce 3+ peak area/Ce 4+ peak area is summarized in Table S2.…”
Section: Growth Process and Properties Of Synthetic Cerium Oxide Nanomentioning
confidence: 99%